OIL PROPERTIES AS INFLUENCED BY AGRONOMIC MANAGEMENT OPTIONS ON VARIOUS RICE VARIETIES GROWN UNDER SALINE IRRIGATION WATER - BOTHA PRASHANTHI; K. SURESH; V. RAMULU; S. SRIDEVI (The Bioscan, 2020)
A field experiment was carried out to investigate the influence of agronomic management options in various rice varieties under saline irrigation water during kharif 2018 at College Farm, College of Agriculture, Rajendranagar, Hyderabad. Slight insignificant decrease in mean pH was observed with In situ green manuring (7.38) and FYM application (7.37) plots. Maximum reduction in EC was noticed with In situ green manuring (0.86 dSm -1 ) which was significantly superior over FYM application (1.06 dSm -1 ), leaching of salts with irrigation water (1.24 dSm -1 ) and control (1.51 dSm -1 ). Among the management practices, In situ green manuring recorded maximum organic carbon (0.53%) which was on par with FYM application (0.51 %), The highest available nitrogen was recorded with In situ green manuring (278.20 kg N ha -1 ) followed by FYM application (273.91 kg N ha -1 ). Significantly the highest available phosphorus was recorded by the In situ green manuring (43.51 kg P 2 O 5 ha -1 ) than the other management practices. A build up of available potassium (1.19 to 9.59 %) was noticed in all the management practices. No significant differences were observed when different varieties were raised in sub plots. The results of the present study indicated that In Situ green manuring was the best among all the treatments tested to mitigate the adverse effect of the poor quality water.